Evaluation of Two Techniques for Transverse Exposure in Obese Patients Undergoing Cesarean Section: A Comparative Study - Banafsheh Madhak; Leila Sadati; Sedigheh Nosrati; Hojat Torkmandy (Golestan University Of Medical Sciences, 2017)
Introduction One of the greatest challenges of the 21st century is the high prevalence of obesity in different age groups. Statistics have shown that pregnant women with body mass index greater than 40 kg/m2 are more likely to have Cesarean section (C-section). The secondary outcomes of the new method and the routine method (using leukoplast tape) were compared by surveying the surgery team on their satisfaction with each tool for surgical site exposure in women undergoing C-section compared to leukoplast tape.  Materials and Methods: This study was conducted on 130 obese patients undergoing C-section at the Kamali Hospital in Alborz Province (Iran) during 2016. Trained operating room personnel completed two checklists designed for assessing satisfaction.  Other variables were assessed via personal observation and surveying the surgical team. Time elapsed until fetal expulsion and from fetal expulsion to wound closure, and the total duration of the surgery were accurately calculated and recorded in the intervention and control groups. Results: The mean number of regular and long gauzes used in the intervention group (15.98±3.5 and 3.65±1) was significantly lower than that of the control group (19.8±5.1 and 4.32±1.1). Time elapsed from fetal expulsion to wound closure was significantly shorter in the intervention group compared to the control group (P<0.001). Conclusions: Given the increased prevalence of obesity in pregnant women undergoing elective C-section and the positive outcomes of this new method, it is recommended to use the method for these surgical procedures.